Assume the following are isomorphic:

Prove |G| = |H|

Prove "phi"(eG) = eH.

Prove "phi"(a^n) = ("phi"(a))^n.

Printable View

- Mar 16th 2009, 12:50 PMpila0688abstract
Assume the following are isomorphic:

Prove |G| = |H|

Prove "phi"(eG) = eH.

Prove "phi"(a^n) = ("phi"(a))^n. - Mar 16th 2009, 02:56 PMSimonM
Let be an isomophism between G and H.

is a bijection, what does that tell you about |G| and |H|?

What does this tell you about ?

Can you induct on a similar expression that I've used above?